OPTIMIZATION OF TURNING PARAMETERS USING AN ALGORTIM BASED ON COMBINED LINEAR AND BINARY SEARCH METHODS - DAN GEORGE PRUTICA; GHEORGHE BRABIE; BOGDAN CHIRITA (Journal of Engineering Studies and Research)
Optimization of cutting parameters in machining operations is a complex task requiring extensive knowledge and experience to reach the maximum potential for cost reductions in manufacturing. Through the work presented in this paper a cutting parameters optimization algorithm for roughing and finishing turning has been realized. The proposed optimization algorithm is based on a combination of linear search and binary search methods, heaving as objective criterion the minimization of the machining time. Examples for roughing and finishing turning have been presented to illustrate the application of the proposed algorithm and analyse the results.